PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP PERILAKU KEWARGAAN ORGANISASI (PKO): PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP PERILAKU KEWARGAAN ORGANISASI (PKO) - Hizrani, Hizrani; Bakti, Dadang Karya; Saptiani, Fenny (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determinate how much the effect of job satisfaction, organizational commitment and leadership style on organizational citizenship behavior. This study uses quantitative approach and takes sample by using purposive sampling technique. The sample consist of 72 employees of PT Siger Jaya Sentosa. The method of analysis use partial or statistical t and simultan or f test. The type of data used in this research was primary and secondary data. The result of this research show that job satisfaction has a positive effect on organizational citizenship behavior, organizational commitment has a positive effect on organizational citizenship behavior and leadershi style has a negative effect on organizational citizeship behavior also simultaneously job satisfaction, organizational commitment and leadership style have an effect of 34,3% on organizational citizenship behavior.